El cuento fantástico como herramienta didáctica para el fortalecimiento de la oralidad en estudiantes de tercer grado de primaria en una institución pública de Bogotá - López Álvarez, Erika (Universidad Antonio Nariño, 2024)
This project aims to strengthen orality in third grade students of a public institution in Bogotá, through the fantastic tale and the use of some oral communication techniques such as the round table and the debate. According to the results of a Language diagnostic test, in which students showed difficulties at exposing and arguing, a didactic unit is proposed based on the stories of Pumi, "The elf carpenter ´elf ”, written by Ellis Kaut.